Scholarly reference trees - Kristina Kocijan; Marko Požega; Dario Poljak (Libellarium: Journal for the Research of Writing, Books, and Cultural Heritage Institutions, 2017)
In this paper, we propose, explain and implement bibliometric data analysis and visualization model in a web environment. We use NLP syntactic grammars for pattern recognition of references used in scholarly publications. The extracted information is used for visualizing author egocentric data via tree like structure. The ultimate goal of this work is to use the egocentric trees for comparisons of two authors and to build networks or forests of different trees depending on the forest’s attributes. We have stumbled upon many different problems ranging from exceptions in citation style structures to optimization of visualization model in order to achieve an optimal user experience. We will give a summary of our grammars’ restrictions and will provide some ideas for possible future work that could improve the overall user experience. The proposed trees can function by themselves, or they can be implemented in digital repositories of libraries and different types of citation databases.